Prevalence of risk factors for HIV infection among Mexican migrants and immigrants: probability survey in the north border of Mexico Prevalencia de factores de riesgo para la infección por VIH entre migrantes mexicanos: encuesta probabilística en la frontera norte de México - M. Gudelia Rangel; Ana P. Martínez-Donate; Melbourne F. Hovell; Jorge Santibáñez; Carol L. Sipan; Jose A. Izazola-Licea (Instituto Nacional de Salud Pública, 2006)
OBJECTIVE: To estimate the prevalence of risk factors for HIV infection among Mexican migrants and immigrants (MMIs) in different geographic contexts, including the sending communities in Mexico, the receiving communities in the United States (US), and the Mexican North border region. MATERIAL AND METHODS: We conducted a probability survey among MMIs traveling through key border crossing sites in the Tijuana (Baja California, Mexico)-San Diego (California, US) border region (N=1 429). RESULTS: The survey revealed substantial rates of reported sexually transmitted infections, needle-sharing and sexual risk practices in all migration contexts. CONCLUSIONS: The estimated levels of HIV risk call for further binational research and preventive interventions in all key geographic contexts of the migration experience to identify and tackle the different personal, environmental, and structural determinants of HIV risk in each of these contexts. OBJETIVO: Estimar la prevalencia de prácticas de riesgo para la infección por VIH en migrantes mexicanos durante su estancia en distintos contextos geográficos, incluyendo sus comunidades de origen en México, las comunidades de destino en Estados Unidos de América (EUA), y la frontera Norte de México. MATERIAL Y MÉTODOS: Encuesta probabilística de migrantes mexicanos que transitan por la región fronteriza Tijuana (Baja California, México)-San Diego (California, EUA) (N=1 429). RESULTADOS: La encuesta reveló una alta prevalencia de infecciones de transmisión sexual, uso compartido de agujas, y prácticas sexuales de riesgo en todos los contextos geográficos estudiados. CONCLUSIONES: Los niveles de riesgo de infección por VIH estimados para migrantes mexicanos en diferentes contextos geográficos exigen estudios e intervenciones preventivas binacionales que identifiquen y aborden los distintos factores de riesgo personales, ambientales, y estructurales que contribuyen al riesgo de infección por VIH en cada contexto.